Field evaluation of dynamic adjust control and PV-based AHU load management using five-minute monitoring data in Thailand - Titayanurak, Ratchata; Teparos, Watchara; Photharin, Somkuan; Wongmeekaew, Tanomsak; Sonsupap, Somchai (Edelweiss Applied Science and Technology, 2026)
This study evaluates dynamic_adjust control for photovoltaic (PV)-assisted Air Handling Unit (AHU) load management using five-minute field monitoring data from an industrial energy system in Thailand. The evaluated system consisted of a utility grid connection, smart meter, PV array, hybrid inverter, AHU load, control box, and mobile monitoring interface. Full-month dynamic_adjust datasets from March and April 2026 were analyzed to examine longer-term operation, while May 1–7 dynamic_adjust data were compared with May 8–14 manual_off data. After data cleaning, the March and April datasets contained 19 and 25 valid operating days, respectively. April showed more stable grid behavior than March, with peak grid demand decreasing from 4.96 to 2.18 kW and P95 grid demand decreasing from 2.30 to 0.83 kW. In the weekly comparison, dynamic_adjust reduced peak grid demand from 2.42 to 1.03 kW, representing a 57.4% reduction. Daily grid energy decreased by 16.9%, and time above the 0.70 kW threshold decreased by 92.2%. The results provide field evidence that dynamic_adjust control can improve grid power stability and support electricity cost reduction in PV-based AHU load management.